2022
DOI: 10.31234/osf.io/bh6tk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anxiety and Emotion Regulation in Young People with Williams Syndrome and Down Syndrome During the COVID-19 Outbreak: A Global Study

Abstract: Young people with neurodevelopmental conditions (NDCs) have been reported to experience increased levels of anxiety during the COVID-19 pandemic. In our study, we document how young people with Down Syndrome (DS; N=557) and Williams syndrome (WS, N=247) experienced the first wave of the COVID-19 pandemic across the world. Using multilevel linear mixed regressions, we studied (a) parental reported anxiety of young people with DS and WS, (b) these young people’s specific concerns, and (c) their use and efficacy … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Survey data indicated that individuals with Williams syndrome had greater anxiety severity compared to individuals with DS. Anxiety severity increased with age and the most common concerns among the Williams syndrome population included the loss of social contact, not being able to approach others, the loss of routine, and fears of becoming ill with COVID-19 [24]. .…”
Section: Anxietymentioning
confidence: 99%
See 3 more Smart Citations
“…Survey data indicated that individuals with Williams syndrome had greater anxiety severity compared to individuals with DS. Anxiety severity increased with age and the most common concerns among the Williams syndrome population included the loss of social contact, not being able to approach others, the loss of routine, and fears of becoming ill with COVID-19 [24]. .…”
Section: Anxietymentioning
confidence: 99%
“…gun shots, fireworks, balloons popping); excessive concerns about death and dying; vomiting phobias; worries about family members arguing; and the fear of medical procedures [23]. Another study utilized a parent-completed online survey to compare anxiety levels between patients with Down syndrome (DS) ( n = 557) and Williams syndrome ( n = 247) from 33 countries during the early stages of the COVID-19 pandemic (April--August 2020) [24]. Survey data indicated that individuals with Williams syndrome had greater anxiety severity compared to individuals with DS.…”
Section: Recent Findingsmentioning
confidence: 99%
See 2 more Smart Citations